Reflections on citizenship. A new hypothesis: the non-citizenship - Alamanni, Andrea (2012)
The reflection on citizenship in Europe is the central element of the article. The historical development of thinking relatedto the concept of citizenship in Europe, from the time of the Greek polis, through the philosophical architecture after theAge of Enlightenment, until reaching the current debate on the whole continent, has led me to make a hypothesis about anew dimension of relationship between the public and private spheres, a new relationship between the people who are born inthe territory of a State or migrate there, A hypothesis that develops a final thesis linked to the residence concept.Citizenship of A series and B series, within the second category are usually women, minors, non citizens and people withphysical disabilities. Citizenship and human lives tied to the concept of blood right, or to a more inclusive place right.Universal human rights and rights "mutilated" by the States; provided that a new relationship between the people and theState is not re-established, between entities that are always changing, between entities that are always changing, and anessentially static concept, that has to be changed already.